2016
DOI: 10.1177/1528083716662587
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the parameters affecting pressure characteristics of medical stockings

Abstract: Compression stockings, which constitute one of the most important groups of compression garments, are engineered to regulate blood flow in venous systems in order to use in many medical fields such as supporting muscles and preventing edema. In the present study, it was aimed to analyze the effects of production parameters such as tightness, elastane yarn feeding tension and elastane yarn counts on pressure behavior of compression stockings, which are commonly used to adjust pressure values. The results of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…This was also verified by the study of Maleki et al. 5 However, in Sari and Oğlakcıoğlu's work, 8 the elastane yarn count was a main factor affecting the pressure value. This could be explained by the different style of stockings (longer stockings were fabricated in their work) and the type of raw material.…”
Section: Resultssupporting
confidence: 53%
See 1 more Smart Citation
“…This was also verified by the study of Maleki et al. 5 However, in Sari and Oğlakcıoğlu's work, 8 the elastane yarn count was a main factor affecting the pressure value. This could be explained by the different style of stockings (longer stockings were fabricated in their work) and the type of raw material.…”
Section: Resultssupporting
confidence: 53%
“…For studying the origin of “structure-properties” problems, the fabrication process was lucubrated. Sari and Oğlakcıoğlu 8 studied the influence of production parameters, such as tightness, elastane yarn feeding tension and elastane yarn counts, on the pressure behavior of GCS. They found that elastane yarn count is the most effective parameter for pressure values.…”
mentioning
confidence: 99%
“…For predicting the pilling tendencies of cotton interlock knitted fabrics, Kayseri used both regression analysis and artificial neural network methods in their studies (23,24). Sari and Oglakcioglu also used regression analysis in their study about pressure characteristics of medical stockings (25). Not only for cotton yarns, cotton waste containing yarn properties were also tried to be explained by using correlation with fiber properties by Telli and Babaarslan (26).…”
Section: Introductionmentioning
confidence: 99%
“…Most scholars in this area demonstrated that knitted garments are the most commonly used fabric in medical and sports hosiery (Mikučionienė & Milašiūtė, 2017; Thomas, 2014). This result is based on the stretch ability and high elasticity of the knitted garment, which makes it more comfortable and efficient (Bera et al, 2016; Loginov, Grishanov, & Harwood, 2002; Liu, Lao, & Wang, 2013; Sarı & Oğlakcıoğlu, 2018). The most outstanding characteristics of elastic compression garments are conserving body shape in addition to their own durability.…”
mentioning
confidence: 99%